ENTREPRENEURHIP PROCLIVITY: AN EXPLANATORY STUDY ON STUDENTS ENTREPRENEURIAL INTENTIONS BY USING THEORY OF PLANNED BEHAVIOUR - Mailoor, Dave Jackson; Pangemanan, Sifrid; Pandowo, Merinda (FEB Universitas Sam Ratulangi Manado, 2014)
Entrepreneurial attitude and entrepreneurial self-efficacy are considered as important factors affecting the intention to step into the process of entrepreneurship. Despite the large number of studies on entrepreneurial intention among university students, there is a lack understanding of factors that lead entrepreneurial intention among engineering students. This research aims to examine the factors that contribute entrepreneurial intention in entrepreneurship by using the Theory of Planned Behavior (TPB) of Fishbein and Ajzein. This study was conducted in University of Sam Ratulangi particularly in Faculty of Business and Economics, International business Administration Program at Manado. Data were analyzed using descriptive and inferential statistics. The result shows that the theory of planned behavior is proven averagely significant to predict students’ entrepreneurial intention simultaneously in University of Sam Ratulangi International business Administration Program. Among the three determinants in TPB that were examined, the highest mean score was recorded is perceived behavioral control. Keywords: entrepreneurship, theory of planned behavior, entrepreneurial intention